Partition and the Visual Arts: Reflections on Method. Issue 2 (4th May 2017) - Mathur, Saloni
Abstract: What are the challenges of Partition for the narratives of art history in the subcontinent today? What kinds of methods of analysis and modes of understanding are necessary to confront the indeterminate, yet proliferating forces of this experience? And what is the role of contemporary art in relation to the new critical historiography of Partition? This article responds to these questions through a consideration of two crucial themes – the status of history and the problem of the border – which signal numerous temporal and spatial dilemmas related to Partition's imprint upon the subcontinent today. By engaging with the tropes of history and the border, the article considers some of the possibilities (and limitations) of certain orientations towards Partition vis-á-vis the visual arts, and points ultimately to the intellectual necessity for a more rigorously dialectical approach.